Kia Tāwharautia Te Mātauranga Māori: Decolonising the Intellectual Property Regime in Aotearoa New Zealand - Kapa-Kingi, Eru (Victoria University of Wellington Law Review, 2020)
This article explores ways to decolonise aspects of the intellectual property system in Aotearoa New Zealand, primarily in respect of trade marks. It considers the seminal Wai 262 report of the Waitangi Tribunal and builds upon its findings and recommendations, while also offering new ideas of legal reform for protecting mātauranga Māori (Māori knowledge and expertise) from undue exploitation. This article also measures those ideas against the objectives and principles of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement), as well as other internationally recognised rights. Essentially, this article maintains that for any mechanism to be effective in recognising and upholding the tino rangatiratanga (unqualified self-determination) of Māori over their own mātauranga, that mechanism must be founded upon the principles of tikanga Māori (Māori laws and customs), which is a notion crystallised within the Treaty of Waitangi/Te Tiriti o Waitangi. It must also find its own meaningful place in the law of New Zealand that surrounds us today. It is only in this way that the extractive and thereby oppressive binds of the western intellectual property regime can be unpicked and put aside and the tapu (high status and associated sanctity) of mātauranga can be upheld. These words are also an honouring of those who spent countless hours on the Wai 262 report. It is hoped this article gives new and much needed life to the issue of protecting mātauranga Māori, which is still as relevant today as it was then. Kei aku rangatira, kei aku tapaeru, kei aku whakaruakākā, tēnei e ngākau whakaiti nei (an acknowledgement of all those who took part in Wai 262).